Cost-Effectiveness of the Pharmacist-Managed Warfarin Therapy vs. Standard Care for Patients With Mechanical Mitral Valve Prostheses: An Egyptian Healthcare Perspective - Batran, Radwa Ahmed; Sabri, Nagwa Ali; Ali, Ihab; Fahmy, Sarah Farid (Frontiers in Cardiovascular Medicine, 2022)
Background Despite warfarin therapy had been used for decades for patients with mechanical mitral valve prostheses (MMVPs), serious and life-threatening complications are still reported worldwide with a significant economic burden. This study is aimed at assessing the clinical and the cost-effectiveness of adopting pharmacist-managed warfarin therapy (PMWT) services for optimizing warfarin treatment in Egypt. Methods A prospective randomized trial in which 59 patients with MMVPs were randomly assigned to receive the PMWT services or the standard care and followed up for 1 year. The primary outcome was percentage time in the therapeutic range (TTR). For the cost-effectiveness analysis, a Markov cohort process model with nine mutually exclusive health states was developed from a medical provider’s perspective. A lifetime horizon was applied. All costs and outcomes were discounted at 3.5% annually. Results The study results revealed a significantly higher median TTR in the intervention group as compared to the control group; 96.8% [interquartile range (IQR) 77.9–100%] vs. 73.1% (52.7–95.1%), respectively, p = 0.008. A significant association between standard care and poor anticoagulation control (p = 0.021) was demonstrated by the multivariate regression analysis. For the cost-effectiveness analysis, the total cumulative quality-adjusted life-years (QALYs) and total costs per patient were 21.53 and 10.43; 436.38 and 1,242.25 United States dollar (USD) in the intervention and the control groups, respectively, with an incremental cost-effectiveness ratio (ICER) of −72.5796 for the intervention group. Conclusion The PMWT strategy was proven to provide a significantly better anticoagulation control and to be a cost-saving approach in Egyptian patients with MMVPs. Nevertheless, the dominance of this strategy is sustained by maintaining the therapeutic International Normalized Ratio (INR) control within the recommended range. Our findings will benefit Egyptian policy-makers who may seek novel health strategies for better resource allocation. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT04409613].